2021
DOI: 10.1039/d0sm01758b
|View full text |Cite
|
Sign up to set email alerts
|

More than just a barrier: using physical models to couple membrane shape to cell function

Abstract: Physical models can help us to infer, from the shape of the outer membrane, which biological processes happen inside the living cell.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 207 publications
0
18
0
Order By: Relevance
“…It has been suggested theoretically that the shape of lipid bilayer vesicles is given by their minimal energy configuration [35,39,58]. Moreover, it has been shown that by increasing the preferred curvature and decreasing the reduced volume, vesicles can get divided [30,32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested theoretically that the shape of lipid bilayer vesicles is given by their minimal energy configuration [35,39,58]. Moreover, it has been shown that by increasing the preferred curvature and decreasing the reduced volume, vesicles can get divided [30,32].…”
Section: Discussionmentioning
confidence: 99%
“…In this paper, we theoretically investigate the interplay between shape changes and membrane trafficking during cytokinesis, following the assumption that the interior of the cell can be inferred from modeling membrane deformations [35]. Our analysis consists of two steps.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike other approaches 72 , Ψ does not allow for a direct control of the bilayer curvature but is rather an indirect mechanism analogous to the protein-membrane surface interplay, as previously described for α-synuclein 13,36 and the N-BAR domain 52 , both known for inducing curvature in lipid bilayers 57,74 . Besides, the complex saddle-shape mode in which the bilayer bends follows two principal curvatures defined by two fitted circles with different radii 3,4,22 and requires significantly more energy than other modes of simpler geometry.…”
Section: Segregation and Opening Are Coupled Eventsmentioning
confidence: 99%
“…Micro-and nano-particles interacting with cell membranes made of lipid bilayers may induce membrane poration, rupture, particle engulfment or simply repulsion [1][2][3][4]. Hence, understanding and controlling particle-lipid membrane interaction is crucial for drug delivery, microbial infection, toxicity from microplastics and in many other fields [1].…”
Section: Introductionmentioning
confidence: 99%